Gamification of telematics data to enhance operators' behaviour for improvement of machine productivity in loading cycles - Rajabi, Milad (Karlsruher Reihe Technologie und Management im Baubetrieb, 2023)
Construction industry is suffering from low productivity rate in various projects such as excavation. Although this issue is discussed in literature and several approaches are proposed to address it, productivity rate is still low in construction industry compared to other domains like manufacturing. A gamified platform in which different operators from different organizations can share their achievements, or can get scored and ranked in a leader-board will potentially address this issue.